Kyrgyz Republic : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Modification of Quantitative Performance Criteria; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Kyrgyz Republic. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
The paper discusses key findings of the Fourth Review Under the Poverty Reduction and Growth Facility (PRGF) for the Kyrgyz Republic. Output is rebounding and inflation remains subdued. However, most end-December 2006 and end-March 2007 structural benchmarks have been missed, partly because of political tensions that slowed the legislature. The 2007 program, which targets 6 1\2 percent output growth and 5 percent inflation, caps the fiscal deficit at 3.1 percent of GDP and maintains a prudent monetary policy. The government plans to implement delayed structural measures under the program, and strengthen external debt management.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet